DYNAMIC SUPPLY RESPONSE : IMPLICATIONS FOR INDONESIA SOYBEAN CROP - Edison, Edison; Dharia Renate; Denny Denmar (Dinasti Publisher, 2020)
The purpose of the study is to explore the supply response model of the soybean crop in terms of alternative specifications also implications economics. To apply model, considerations through the availability of production lags concept also the existence of expected price and gross revenue because of producer’s response explanatory preference on movement economic situation. The results showed that the existing lags were due mostly to the problems also quick adjustment expenditure rather than correcting expected time. The quantitative result was the same as gross margins and prices alternative specification as the availability of economic decisions. Meanwhile, elasticities price found through the model response specification tended around a fourth of the model applying price specification. The model response specification produced more explanation in terms of production also elasticity of input expenditure.